HIF-Dependent NFATC1 Activation Upregulates ITGA5 and PLAUR in Intestinal Epithelium in Inflammatory Bowel Disease - Knyazev, Evgeny; Maltseva, Diana; Raygorodskaya, Maria; Shkurnikov, Maxim (Frontiers in Genetics, 2021)
Intestinal epithelial cells exist in physiological hypoxia, leading to hypoxia-inducible factor (HIF) activation and supporting barrier function and cell metabolism of the intestinal epithelium. In contrast, pathological hypoxia is a common feature of some chronic disorders, including inflammatory bowel disease (IBD). This work was aimed at studying HIF-associated changes in the intestinal epithelium in IBD. In the first step, a list of genes responding to chemical activation of hypoxia was obtained in an in vitro intestinal cell model with RNA sequencing. Cobalt (II) chloride and oxyquinoline treatment of both undifferentiated and differentiated Caco-2 cells activate the HIF-signaling pathway according to gene set enrichment analysis. The core gene set responding to chemical hypoxia stimulation in the intestinal model included 115 upregulated and 69 downregulated genes. Of this set, protein product was detected for 32 genes, and fold changes in proteome and RNA sequencing significantly correlate. Analysis of publicly available RNA sequencing set of the intestinal epithelial cells of patients with IBD confirmed HIF-1 signaling pathway activation in sigmoid colon of patients with ulcerative colitis and terminal ileum of patients with Crohn’s disease. Of the core gene set from the gut hypoxia model, expression activation of ITGA5 and PLAUR genes encoding integrin α5 and urokinase-type plasminogen activator receptor (uPAR) was detected in IBD specimens. The interaction of these molecules can activate cell migration and regenerative processes in the epithelium. Transcription factor analysis with the previously developed miRGTF tool revealed the possible role of HIF1A and NFATC1 in the regulation of ITGA5 and PLAUR gene expression. Detected genes can serve as markers of IBD progression and intestinal hypoxia.